Indonesia : Report on the Observance of Standards and Codes-Fiscal Transparency Module-Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Indonesia has improved fiscal transparency; tax legislation has been substantially revised; tax administration is improving; legal and administrative measures have been adopted to improve public sector governance; and important steps have been taken to rationalize government banking arrangements. However, much remains to be done to improve transparency. There is a large but crucial agenda to improve the monitoring of subnational budgetary and debt developments so as to improve the transparency and quality of fiscal policy at the general government level.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet